2011
DOI: 10.1007/s12282-011-0263-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative prediction of tumor response to neoadjuvant chemotherapy in breast cancer: novel marker genes and prediction model using the expression levels

Abstract: A study to validate the predictive values of the selected 4 genes is now planned, along with research to determine their functional roles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…It has been shown that docetaxel may have anti-angiogenic activity by reducing the synthesis of pro-angiogenic molecules (such as bFGF and VEGF) in cancer cells28. In addition, it was recently discovered that conventional cytotoxic chemotherapy can mobilize endothelial precursor cells, and hence, play an important role in inhibiting neovascularization and tumor growth29.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that docetaxel may have anti-angiogenic activity by reducing the synthesis of pro-angiogenic molecules (such as bFGF and VEGF) in cancer cells28. In addition, it was recently discovered that conventional cytotoxic chemotherapy can mobilize endothelial precursor cells, and hence, play an important role in inhibiting neovascularization and tumor growth29.…”
Section: Discussionmentioning
confidence: 99%
“…22 The scanned image data were analyzed with Agilent Feature Extraction software (version 9.5, Agilent Technologies), and gene expression signals were normalized using GeneSpring GX (Agilent Technologies) and further analyzed using Spotfire software (Tibco Software).…”
Section: Dna Microarray Analysismentioning
confidence: 99%
“…Recently, a series of investigation in DUSPs defined essential roles in cell proliferation and cancer [17][18][19][20][21][22][23] and their immune response. 4,24 Although there are at least 11 MKPs (many of them were thought to have a similar role to regulate MAPK cascades), it is obvious that each of them has different substrate specificities and physiological roles.…”
Section: Introductionmentioning
confidence: 99%